Synthesis and Antitumor Activity of Novel 1-Substituted 3-(4,5-Substituted 1,2,4-Triazol-3-yl)-β-carboline Derivatives - Brand, George; Gomes, Carla M. B.; Costa, Willian F.; Foglio, Mary A.; Ruiz, Ana L. T. G.; Sarragiotto, Maria H. (Synthesis, 2019)
Schiff bases, 1,2,4-triazolo[4,3-d][1,2,3,4]thiatriazoles, and 1,2,4-triazolo[3,4-b][1,3,4]thiadiazoles carrying the β-carboline nucleus were synthesized from 3-(4-amino-5-mercapto-1,2,4-triazol-3-yl)-β-carbolines. The compounds were evaluated for their in vitro antitumor activity against eight human cancer cell lines. The 1,2,4-triazolo[4,3-d][1,2,3,4]thiatriazole derivatives showed a broad spectrum of antitumor activity, with GI50 values lower than 13 μM for all cell lines tested. In general, all tested compounds showed potent activity against the breast (MCF-7) cancer cell line, with GI50 values in the range of 2.07 to 4.58 μM.
Keywords: β-carbolines; 4,5-substituted 1,2,4-triazoles; Schiff bases; 1,2,4-triazolo[4,3-d][1,2,3,4]thiatriazoles; antitumor activity